Renal perfusion phase curve analysis in DTPA renal scintigraphy – significance & utility - Sivasubramaniyan, V; Sai, Osho; Venkataramaniah, K (Asian Journal of Medical Sciences, 2015)
Aims and Objectives: The retrospective study of renal scans aims at analysing the renal perfusion phase curve in the DTPA scan. Four different types of perfusion phase curves for non-transplant kidney are defined and validated by comparing them with the Hilson perfusion index and Kirchner’s K/A ratio. Materials and Methods: This study consists of 36 patients comprising of 26 males with mean age of 26.17 ± 18.65 and 10 females with the mean age of 33.20 ± 11.69. Renal scans were done using Siemens dual head gamma camera. 3-5mCi 99m Tc DTPA was used and injected intravenously, images were processed to obtain the renal curve using the icon software utilizing the Gate’s formula. The perfusion curves, which form the part of renographic curves are taken for scrutiny, are classified into different types and perfusion index was calculated. Results: The perfusion phase curves were scrutinised and categorised in 4 types. These curves have been validated by using Hilson index and Kirchner’s K/A ratio. Hilson perfusion index and Kirchner’s K/A ratio shows a good correlation with the uptake phase of conventional renal curve. We observed 47.22% of Type I, 22.22% of Type II, 16.67% of Type III and 13.89% of Type IV. Conclusion: This study highlights the utility of renal perfusion phase curve analysis in the non-transplant kidney. This can also serve as a better prognostic tool in the chronic kidney disease patient. Asian Journal of Medical Sciences Vol.7(2) 2015 44-48